4
$\begingroup$

Is either of these inequalities true? $$\lambda(tA + (1-t)B)\geq t\lambda(A) + (1-t)\lambda(B)$$ or $$\lambda(tA + (1-t)B)\leq t\lambda(A) + (1-t)\lambda(B),$$ where $0\leq t \leq 1$, $A,B$ are bounded domains in $\mathbb{R}^n$ and $\lambda(\Omega)$ is an eigenvalue of the problem $$-\Delta\,u=\lambda\,u\,\,\mbox{in}\,\,\, \Omega, \, u=0\,\,\,\mbox{on}\,\,\, \partial\Omega.$$

$\endgroup$
4
$\begingroup$

Update: I intended this to be a complete answer originally, but my "counterexample" was based on a miscalculation. So this is now more a collection of remarks on what I think the question is about.

We need to be more specific about which eigenvalue we want to take. I will discuss the ground state energy, which seems natural.

The first inequality is clearly false because $\lambda(\Omega)$ becomes large when we make the region small. As for the second, I want to rename $A'=tA$, $B'=(1-t)B$ (and then drop the primes again). Then the claim becomes $$ \lambda(A+B) \le t^3\lambda (A) + (1-t)^3 \lambda(B) , $$ for all $0\le t\le 1$. Minimize over $t$ to rewrite this as $$ \lambda(A+B) \le \frac{\lambda(A)\lambda(B)}{(\sqrt{\lambda (A)} + \sqrt{\lambda (B)})^2} . \quad\quad\quad\quad (1) $$ This is true in one dimension, with equality; recall that $\lambda([0,L])=\pi^2/L^2$ to see this. I don't know what happens in higher dimensions; preliminary attempts at easy counterexamples (rectangles ...) were unsuccessful, and if I had to guess, I would now say that (1) is probably true. The inequality does hold in the special case $A=B$ (because then $A+A\supseteq 2A$).

$\endgroup$
  • $\begingroup$ Please, Christian Remling, you can give me some reference. $\endgroup$ – de Araujo Jun 4 '15 at 22:17
  • $\begingroup$ @deAraujo: References on what exactly? I'm not really using anything in this answer. $\endgroup$ – Christian Remling Jun 4 '15 at 22:22
  • $\begingroup$ Please, you could explain to me again how it obtained the expression $\lambda(A+B)\leq t^3\lambda(A) + (1-t)^3\lambda(B)$. $\endgroup$ – de Araujo Jun 4 '15 at 22:29
  • $\begingroup$ @deAraujo: Use that $\lambda (tC)=t^{-2}\lambda (C)$, which just follows from the definitions: if $u(x)$ solves $-\Delta u=\lambda u$ on $C$, then $u(x/t)$ works on $tC$ and vice versa. $\endgroup$ – Christian Remling Jun 4 '15 at 22:31
  • $\begingroup$ Right, note that (1) is also true, with equality, for $\lambda_k([0,L])=\pi^2k^2/L^2$, for each $k\geq 1$ integer. $\endgroup$ – de Araujo Jun 5 '15 at 0:23

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.